2021
DOI: 10.1111/tri.13983
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective single‐centre analysis of the oncological impact of LI‐RADS classification applied to Metroticket 2.0 calculator in liver transplantation: every nodule matters

Abstract: Although the diagnostic value of Liver Imaging Reporting and Data System (LI-RADS) protocol is well recognized in clinical practice, its role in liver transplant (LT) setting is under-explored. We sought to evaluate the oncological impact of LI-RADS classification applied to Metroticket 2.0 calculator in a single-centre retrospective cohort of transplanted hepatocellular carcinoma (HCC) patients, exploring which LI-RADS subclasses need to be considered in order to grant the best Metroticket 2.0 performance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Thus, we hypothesize that the association of poorer patient outcomes with a lack of complete response after first locoregional session may be due to unfavorable baseline risk factors. It is worth to underline that the study group included only LR-5 tumors, although Centonze et al suggest that including tumors LR-3 and LR-4 in OS prediction does not significantly decrease its precision [26]. Moreover, presented results extend recent suggestions by Wang et al that the best objective response correlates better with treatment outcomes in patients with more advanced disease, as the concordance between initial and overall best response is weak in those subjects [7].…”
Section: Discussionsupporting
confidence: 59%
“…Thus, we hypothesize that the association of poorer patient outcomes with a lack of complete response after first locoregional session may be due to unfavorable baseline risk factors. It is worth to underline that the study group included only LR-5 tumors, although Centonze et al suggest that including tumors LR-3 and LR-4 in OS prediction does not significantly decrease its precision [26]. Moreover, presented results extend recent suggestions by Wang et al that the best objective response correlates better with treatment outcomes in patients with more advanced disease, as the concordance between initial and overall best response is weak in those subjects [7].…”
Section: Discussionsupporting
confidence: 59%
“…The Liver Imaging Reporting and Data System (LI-RADS) has recently been developed and has evolved as a comprehensive and standardized diagnostic algorithm for HCC imaging reporting [ 6 ]. LI-RADS has been proven to be an effective tool not only for HCC diagnosis but also for outcome prediction after liver resection, radiofrequency ablation, or liver transplantation [ 6 , 7 , 8 ], exerting an increasing influence on the treatment management of HCC. Previous studies have demonstrated the diagnostic value of LI-RADS in the prediction of MVI [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, although qFibrosis can provide more accurate fibrotic status than conventional histological methods, sampling error may still have some influence on the qFibrosis score. Besides, our study was unable to provide competing risk analysis as Metroticket 2.0 model used in liver transplantation patients owing to the complicated clinical situations and the study design [ 34 , 35 ]. Finally, our method needs liver tissue to obtain its qFibrosis score, so it is not a non-invasive assessment of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%